NAD+ Metabolism Regulates Preadipocyte Differentiation by Enhancing α-Ketoglutarate-Mediated Histone H3K9 Demethylation at the PPARγ Promoter - Okabe, Keisuke; Nawaz, Allah; Nishida, Yasuhiro; Yaku, Keisuke; Usui, Isao; Tobe, Kazuyuki; Nakagawa, Takashi (Frontiers in Cell and Developmental Biology, 2020)
Obesity has become a serious problem in public health worldwide, causing numerous metabolic diseases. Once the differentiation to mature adipocytes is disrupted, adipocyte hypertrophy and ectopic lipid accumulation leads to the inflammation in adipose tissue and systemic metabolic disorders. Intracellular metabolic state is known to change during cell differentiation and it affects the cell fate or the differentiation through epigenetic mechanism. Although the mechanism of preadipocyte differentiation has been well established, it is unknown how metabolic state changes and how it affects the differentiation in preadipocyte differentiation. Nicotinamide adenine dinucleotide (NAD) plays crucial roles in energy metabolism as a coenzyme in multiple redox reactions in major catabolic pathways and as a substrate of sirtuins or poly(ADP-ribose)polymerases. NAD is mainly synthesized from salvage pathway mediated by two enzymes, Nampt and Nmnat. The manipulation to NAD metabolism causes metabolic change in each tissue and changes in systemic metabolism. However, the role of NAD and Nampt in adipocyte differentiation remains unknown. In this study, we employed liquid chromatography-mass spectrometry (LC-MS)- and gas chromatography-mass spectrometry (GC-MS)-based targeted metabolomics to elucidate the metabolic reprogramming events that occur during 3T3-L1 preadipocyte differentiation. We found that the tricarboxylic acid (TCA) cycle was enhanced, which correlated with upregulated NAD synthesis. Additionally, increased alpha-ketoglutarate (αKG) contributed to histone H3K9 demethylation in the promoter region of PPARγ, leading to its transcriptional activation. Thus, we concluded that NAD-centered metabolic reprograming is necessary for the differentiation of 3T3-L1 preadipocytes.